REBRANDING TELAGA IJO JELANTIK MENJADI WISATA TIRTA DENGAN PENEBARAN IKAN DAN PENANAMAN POHON PENEDUH - Baiq Alfia Rahmatul Aini; Suni, Muhammad Asy’ Arya; Ubudiyah, Sativa; Putra, Wahyuda Mandala; Umri, Ropizar; Haswari, Nanda Ciptaning; Febrian, Baiq Eka; Rodiah, Rodiah; Usiana, Shilan; Maulana, Alvin (Universitas Mataram, 2025)
Telaga Ijo Jelantik is a tourist destination in Jelantik Village, Jonggat District, Central Lombok Regency, which has great attraction but is still little known to tourists outside the area. To increase tourist attraction and ecosystem sustainability, Telaga Ijo Jelantik was rebranded through the distribution of fish seeds and planting shade trees. This activity aims to revitalize sustainable natural resources in the context of disaster mitigation, improving ecosystem balance, as well as developing water water tourism attractions so that they have the potential to attract local tourists. Where the outcome can improve the economy of the local community. Implementation methods include location surveys, preparation of plans, outreach to the community, and publication in online media. The results of this activity show that the rebranding of Telaga Ijo Jelantik was well received by the community, seen from the strong will of POKDARWIS and support from the Jelantik Village Management. Distribution of fish seeds and planting shade trees is effective in increasing community environmental awareness and has the potential to support the growth of the micro-economic and creative sectors in Jelantik Village.